High-toughness carbon steel composite board and preparation process thereof
By designing an outer coating containing copper, zinc and nickel composite components on the carbon steel composite board, and combining with a fine preparation process, the problem of insufficient toughness of traditional carbon steel composite boards is solved, achieving high toughness and excellent comprehensive performance.
Patent Information
- Application Number
- CN202510404989.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-02
AI Technical Summary
Traditional carbon steel composite panels have limitations in toughness, especially in extreme working environments, their comprehensive performance is difficult to meet the needs of complex working conditions.
The design of high-toughness carbon steel composite panels including inner layer of carbon steel, intermediate layer of stainless steel plate and outer layer of toughness coating is adopted. The outer layer of coating is made of copper-zinc nickel composite, tungsten carbide, natural rubber, ethanolamine and deionized water. The uniform dispersion and close bond of each component is achieved through a fine preparation process.
It significantly improves the toughness and wear resistance of composite panels, enhances the ability to resist impact, scratches and wear, while maintaining other excellent properties such as strength and corrosion resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal composite materials and relates to a high-toughness carbon steel composite plate and a preparation process thereof. Background Art
[0002] In the field of materials science, composite plates are widely used in various industrial fields due to their excellent comprehensive properties. Among them, carbon steel composite plates have become one of the preferred materials in many industries due to their high strength, good processing performance and relatively low cost.
[0003] However, traditional carbon steel composite plates still have limitations in toughness, especially in extreme working environments, such as high temperature, high pressure, strong corrosion or high impact load conditions, and their comprehensive performance often cannot meet the needs of complex working conditions. In order to improve the toughness of carbon steel composite plates, researchers have tried a variety of methods, including adjusting the substrate composition, introducing tough alloy elements, optimizing heat treatment processes, and developing new coating technologies.
[0004] Although these methods have improved the toughness of carbon steel composite plates to a certain extent, there are still some problems, such as complex process, high cost, limited improvement in toughness or affecting other properties (such as strength and corrosion resistance). Therefore, developing a high-toughness carbon steel composite plate that can significantly improve toughness while maintaining other excellent properties, with a simple preparation process and controllable cost has become a hot topic in current research.
[0005] The present invention is proposed in this context, and aims to solve the problem of insufficient toughness of traditional carbon steel composite plates through innovative material design and preparation technology. Summary of the invention
[0006] The purpose of the present invention is to provide a high-toughness carbon steel composite plate and a preparation process thereof, which has the characteristics of high toughness.
[0007] The purpose of the present invention can be achieved through the following technical solutions: A high-toughness carbon steel composite plate, comprising an inner layer of carbon steel, a middle layer of stainless steel plate and an outer layer of toughness coating, The outer toughness coating has a formula of 20-30% copper-zinc-nickel compound, 20-30% tungsten carbide, 20-30% natural rubber, 10-15% ethanolamine, and 10-15% deionized water, by mass percentage. The preparation method of the copper-zinc-nickel composite is as follows: S1.1: Copper nitrate pentahydrate, zinc nitrate hexahydrate, and nickel nitrate hexahydrate are mixed in a mass ratio of 5:2:3, and ground at a speed of 300 r / min for 15-30 min, and then 2-3 wt% oxalic acid monohydrate is added, and the grinding is continued for 10-15 min to obtain a uniform and viscous mixture A; S1.2: Mix the mixture A and aqueous ammonia with a concentration of (0.5-1) mol / L in a mass ratio of 1:1, ultrasonicate for 30 min, and dry at 110 °C for 12 h to obtain a mixture B; S1.3: The mixture B is heated from room temperature to 200°C, kept at a constant temperature and then roasted for 1-2 hours, then heated to 350°C, kept at a constant temperature and then roasted for 1 hour, and after roasting, it is crushed and ground to obtain a copper-zinc-nickel composite; The outer toughness coating preparation method is as follows: S2.1: Mix the copper-zinc-nickel composite and tungsten carbide according to the formula ratio, put them into a ball mill and grind them at a speed of 400 r / min for 2 hours to obtain a mixture C; S2.2: Heat the natural rubber to 130-140° C., stir it in a stirrer at a speed of 150 r / min for 1-2 h, add ethanolamine and deionized water according to the formula ratio, increase the stirrer speed to 200 r / min, add mixture C, stir for 3-4 h, and obtain the coating.
[0008] Furthermore, the rate of heating from room temperature to 200° C. in S1.3 is 5° C. / min.
[0009] Furthermore, the rate of heating from 200°C to 350°C in S1.3 is 3°C / min.
[0010] Furthermore, the copper-zinc-nickel composite obtained in S1.3 has a particle size of 100 mesh.
[0011] Furthermore, the particle size of the mixture C in S2.1 is 200 mesh.
[0012] A preparation process of a high-toughness carbon steel composite plate, the specific process of the preparation process of the high-toughness carbon steel composite plate is as follows.
[0013] S3.1: Place the inner carbon steel and the middle stainless steel in a vacuum sealed environment and weld them together. The welding parameters are: welding vacuum degree ≤ 1.0Pa, welding current 80~100A, welding depth 50~80mm under argon atmosphere; S3.2: After welding, the surface of the middle layer stainless steel is polished and ground. After polishing, it is purged with 10m / s nitrogen. After purging, the outer toughness coating is evenly sprayed on the surface of the middle layer stainless steel by spraying method and left to stand for 1~2h; S3.3: The coating is dried by a laser drying method, and then further hot-pressed by a hot pressing method. The hot pressing parameters are a temperature of 60-70°C, an applied force of 10KN-15KN, and a hot pressing time of 120-300s. After hot pressing, it is first purged with 80°C hydrogen for 1 hour, and then purged with 80°C nitrogen for 0.5 hours to obtain the high-toughness carbon steel composite plate.
[0014] Furthermore, the polishing parameters in S3.2 are: first use a grinding head composed of 500-mesh elastic modules to polish at 1-2 MPa for 1 hour, and then use a grinding head composed of 2000-mesh elastic modules to polish at 0.3-0.5 MPa for 0.5 hour.
[0015] Furthermore, the spraying parameters in S3.2 are spraying distance 100 mm and spraying rate 60 mm / s.
[0016] Furthermore, the parameters of the laser drying in S3.3 are laser power 260-300 W, temperature 50-60° C., and irradiation time 20-30 min.
[0017] Furthermore, the purge flow rate of hydrogen and nitrogen in S3.3 is 20 m / s.
[0018] The present invention proposes a high-toughness carbon steel composite plate comprising an inner layer of carbon steel, an intermediate layer of stainless steel plate and an outer layer of tough coating, wherein the outer layer of tough coating adopts a formula of copper-zinc-nickel composite, tungsten carbide, natural rubber, ethanolamine and deionized water, and achieves uniform dispersion and close combination between the components through a sophisticated preparation process. At the same time, the present invention also optimizes the preparation process of the composite plate, including welding, polishing, spraying, laser drying and hot pressing treatment steps, to ensure that the composite plate has excellent comprehensive performance.
[0019] By placing the inner layer of carbon steel and the middle layer of stainless steel in a vacuum sealed environment for welding, and controlling parameters such as welding vacuum, welding atmosphere, welding current and welding depth, oxidation and pollution during welding are significantly reduced, ensuring the quality and strength of the welded joint. After welding, the surface of the middle layer of stainless steel is polished and ground to remove surface defects and dirt generated during welding, and improve the surface finish and flatness. Subsequently, nitrogen is used for purging to further clean the surface, providing a good foundation for the spraying of the outer tough coating. The present invention uses a spraying method to evenly spray the outer tough coating on the surface of the middle layer of stainless steel, and let it stand for a period of time to allow the coating to fully combine with the substrate, thereby improving the adhesion and durability of the coating; the present invention uses a laser drying method to dry the coating, which can remove the solvent and moisture in the coating, avoiding problems such as cracking and falling off of the coating during subsequent processing, and then uses a hot pressing method to further hot press the coating to enhance the bonding between the coating and the substrate, while improving the density of the coating. property and hardness; using hydrogen and nitrogen for purging after hot pressing can further remove residual gas and impurities in the coating, improve the purity and quality of the coating, and utilize the reducing property of hydrogen to reduce the oxides that may exist on the surface of the composite board at high temperature, thereby removing these oxide impurities and ensuring the cleanliness of the surface of the composite board. At the same time, hydrogen purging can also help remove gas residues that may be generated during the hot pressing process, as well as tiny bubbles that may exist between the coating and the substrate, thereby enhancing the bonding force between the coating and the substrate. The surface of the composite board can be further cleaned by nitrogen purging to improve its surface purity and smoothness.
[0020] The present invention prepares a high-toughness carbon steel composite plate including an inner layer of carbon steel, an intermediate layer of stainless steel plate and an outer layer of tough coating, wherein the inner layer of carbon steel provides the main strength and rigidity of the composite plate, so that the composite plate can withstand larger loads and stresses; the intermediate layer of stainless steel plate has good corrosion resistance and oxidation resistance, and can effectively prevent the composite plate from being corroded and oxidized during use, thereby extending its service life; the outer layer of tough coating enhances the toughness and wear resistance of the composite plate, improves its impact resistance, scratch resistance and abrasion resistance, and at the same time improves the surface performance of the composite plate, making it smoother and more beautiful.
[0021] The present invention undergoes the steps of grinding, mixing, drying and roasting, and the copper, zinc and nickel elements react chemically under the action of oxalic acid and ammonia water to form uniform composite particles, which play a role of strengthening and dispersing in the coating. The copper, zinc and nickel composite, as one of the main components of the coating, has excellent electrical conductivity, thermal conductivity and corrosion resistance. In the coating, it can form a dense protective film to prevent the external environment from corroding the composite plate; tungsten carbide is a material with extremely high hardness, which can significantly improve the hardness and wear resistance of the coating. In the coating, the tungsten carbide particles play a role of wear resistance and hardness enhancement, making the composite plate more durable; natural rubber has good elasticity and toughness, which can increase the flexibility and impact resistance of the coating. In the coating, natural rubber plays a role of buffering and shock absorption, so that the composite plate can reduce damage when it is impacted. The natural rubber in the present invention is purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd., item number PB959232.
[0022] During the preparation process, the copper-zinc-nickel composite undergoes grinding, mixing, drying and roasting to form a uniform and dense particle structure. These particles can be closely arranged in the coating to form a continuous network structure, which improves the overall strength and toughness of the coating; tungsten carbide particles can form a wear-resistant "skeleton" in the coating, and together with the copper-zinc-nickel composite, they form a wear-resistant layer, which significantly improves the wear resistance of the coating; the polar groups in natural rubber can form chemical bonds and physical adsorption with the copper-zinc-nickel composite and tungsten carbide particles, thereby improving the adhesion between the coating and the substrate, and this improved adhesion helps the coating form a more solid bond on the surface of the composite plate.
[0023] Ingredients such as copper-zinc-nickel composite, tungsten carbide and natural rubber work synergistically in the coating to jointly improve the hardness, wear resistance and toughness of the coating; the addition of ethanolamine and deionized water enables the various components in the coating to be evenly dispersed in the coating to form a dense coating structure; the uniformity and density of the coating make the surface of the composite board smoother and more beautiful, while improving its scratch resistance and wear resistance.
[0024] Beneficial effects of the present invention: The present invention proposes a high-toughness carbon steel composite plate comprising an inner layer of carbon steel, an intermediate layer of stainless steel plate and an outer layer of tough coating, wherein the outer layer of tough coating adopts a formula of copper-zinc-nickel composite, tungsten carbide, natural rubber, ethanolamine and deionized water, and achieves uniform dispersion and close combination between the components through a sophisticated preparation process; the present invention optimizes the preparation process of the composite plate, including welding, polishing, spraying, laser drying and hot pressing treatment steps, to ensure that the composite plate has excellent wear resistance and toughness. DETAILED DESCRIPTION
[0025] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0026] Coating formula 1: copper-zinc-nickel complex 30%, tungsten carbide 30%, natural rubber 20%, ethanolamine 10%, deionized water 10%; Coating formula 2: copper-zinc-nickel complex 20%, tungsten carbide 20%, natural rubber 30%, ethanolamine 15%, deionized water 15%; Coating formula 3: copper-zinc-nickel complex 25%, tungsten carbide 25%, natural rubber 25%, ethanolamine 10%, deionized water 15%.
[0027] Example 1 The preparation method of the copper-zinc-nickel composite is as follows: S1.1: Copper nitrate pentahydrate, zinc nitrate hexahydrate, and nickel nitrate hexahydrate were mixed in a mass ratio of 5:2:3, and ground at a speed of 300 r / min for 20 min, and then 2 wt% oxalic acid monohydrate was added, and grinding was continued for 10-15 min to obtain a uniform and viscous mixture A; S1.2: Mix mixture A and (1 mol / L ammonia water in a mass ratio of 1:1, ultrasonicate for 30 min, and dry at 110 °C for 12 h to obtain mixture B; S1.3: The mixture B is heated from room temperature to 200°C at a heating rate of 5°C / min, and then calcined for 2 hours at a constant temperature. The mixture is then heated to 350°C at a heating rate of 3°C / min, and then calcined for 1 hour at a constant temperature. After calcination, the mixture is crushed and ground to obtain a copper-zinc-nickel composite having a particle size of 100 mesh. The outer toughness coating preparation method is as follows: S2.1: Mix the copper-zinc-nickel composite and tungsten carbide according to the formula ratio, put them into a ball mill and grind them at a speed of 400 r / min for 2 hours to obtain a mixture C with a particle size of 200 mesh; S2.2: The natural rubber is heated to 135° C. and stirred in a mixer at a speed of 150 r / min for 1 h. Ethanolamine and deionized water are added according to the formula ratio. The mixer speed is increased to 200 r / min. Mixture C is added and stirred for 3 h to obtain the coating.
[0028] A preparation process of a high-toughness carbon steel composite plate, the specific process of the preparation process of the high-toughness carbon steel composite plate is as follows.
[0029] S3.1: Place the inner carbon steel and the middle stainless steel in a vacuum sealed environment and weld them together. The welding parameters are: welding vacuum degree ≤ 1.0Pa, welding current 80A, welding depth 70mm under argon atmosphere; S3.2: After welding, the surface of the middle layer stainless steel is polished and ground. The polishing parameters are: first use a grinding head composed of 500 mesh elastic modules to grind at 2MPa for 1h, then use a grinding head composed of 2000 mesh elastic modules to grind at 0.5MPa for 0.5h. After grinding, use 10m / s nitrogen to purge. After the purge, use the spraying method to evenly spray the outer toughness coating on the surface of the middle layer stainless steel. The spraying parameters are spraying distance 100mm, spraying rate 60 mm / s, and standing for 1h. S3.3: The coating is dried by a laser drying method, the parameters of which are a laser power of 300 W, a temperature of 50°C, and an irradiation time of 20 min. The coating is then further subjected to hot pressing treatment, the parameters of which are a temperature of 70°C, an applied force of 10 KN, and a hot pressing time of 200 s. After hot pressing, hydrogen at 80°C is first used for purging, the hydrogen purging flow rate is 20 m / s, and the purging time is 1 h. Then, nitrogen at 80°C is used for purging, the purging time is 0.5 h, and the nitrogen purging flow rate is 20 m / s, to obtain the high-toughness carbon steel composite plate.
[0030] Example 2 The preparation method of the copper-zinc-nickel composite is as follows: S1.1: Copper nitrate pentahydrate, zinc nitrate hexahydrate, and nickel nitrate hexahydrate were mixed in a mass ratio of 5:2:3, and ground at a speed of 300 r / min for 30 min, and then 3 wt% oxalic acid monohydrate was added and ground for another 10 min to obtain a uniform and viscous mixture A; S1.2: Mix mixture A and 0.5 mol / L ammonia water in a mass ratio of 1:1, ultrasonicate for 30 min, and dry at 110°C for 12 h to obtain mixture B; S1.3: The mixture B is heated from room temperature to 200°C at a heating rate of 5°C / min, and then calcined for 2 hours at a constant temperature. The mixture is then heated to 350°C at a heating rate of 3°C / min, and then calcined for 1 hour at a constant temperature. After calcination, the mixture is crushed and ground to obtain a copper-zinc-nickel composite having a particle size of 100 mesh. The outer toughness coating preparation method is as follows: S2.1: Mix the copper-zinc-nickel composite and tungsten carbide according to the formula ratio, put them into a ball mill and grind them at a speed of 400 r / min for 2 hours to obtain a mixture C with a particle size of 200 mesh; S2.2: The natural rubber is heated to 130° C. and stirred in a mixer at a speed of 150 r / min for 2 h. Ethanolamine and deionized water are added according to the formula ratio. The mixer speed is increased to 200 r / min. Mixture C is added and stirred for 3 h to obtain the coating.
[0031] A preparation process of a high-toughness carbon steel composite plate, the specific process of the preparation process of the high-toughness carbon steel composite plate is as follows.
[0032] S3.1: Place the inner carbon steel and the middle stainless steel in a vacuum sealed environment and weld them together. The welding parameters are: welding vacuum degree ≤ 1.0Pa, welding current 100A, welding depth 80mm under argon atmosphere; S3.2: After welding, the surface of the middle layer stainless steel is polished and ground. The polishing parameters are: first use a grinding head composed of 500 mesh elastic modules to grind at 2MPa for 1h, then use a grinding head composed of 2000 mesh elastic modules to grind at 0.4MPa for 0.5h. After polishing, use 10m / s nitrogen to purge. After purging, use the spraying method to evenly spray the outer toughness coating on the surface of the middle layer stainless steel. The spraying parameters are spraying distance 100mm, spraying rate 60 mm / s, and standing for 2h. S3.3: The coating is dried by a laser drying method, the parameters of the laser drying are a laser power of 260 W, a temperature of 60°C, and an irradiation time of 30 minutes, and then further hot-pressed by a hot-pressing method, the hot-pressing parameters are a temperature of 60°C, an applied force of 15 KN, and a hot-pressing time of 300 seconds. After hot-pressing, hydrogen at 80°C is first used for purging, the hydrogen purging flow rate is 20 m / s, and the purging time is 1 hour, and then nitrogen at 80°C is used for purging, the purging time is 0.5 h, and the nitrogen purging flow rate is 20 m / s, to obtain the high-toughness carbon steel composite plate.
[0033] Example 3 The preparation method of the copper-zinc-nickel composite is as follows: S1.1: Copper nitrate pentahydrate, zinc nitrate hexahydrate, and nickel nitrate hexahydrate were mixed in a mass ratio of 5:2:3, and ground at a speed of 300 r / min for 15 min, and then 3 wt% oxalic acid monohydrate was added and ground for another 15 min to obtain a uniform and viscous mixture A; S1.2: Mix mixture A and 1 mol / L ammonia water in a mass ratio of 1:1, ultrasonicate for 30 min, and dry at 110°C for 12 h to obtain mixture B; S1.3: The mixture B is heated from room temperature to 200°C at a heating rate of 5°C / min, and then calcined for 1 hour at a constant temperature. The mixture is then heated to 350°C at a heating rate of 3°C / min, and then calcined for 1 hour at a constant temperature. After calcination, the mixture is crushed and ground to obtain a copper-zinc-nickel composite having a particle size of 100 mesh. The outer toughness coating preparation method is as follows: S2.1: Mix the copper-zinc-nickel composite and tungsten carbide according to the formula ratio, put them into a ball mill and grind them at a speed of 400 r / min for 2 hours to obtain a mixture C with a particle size of 200 mesh; S2.2: The natural rubber is heated to 140° C. and stirred in a mixer at a speed of 150 r / min for 2 h. Ethanolamine and deionized water are added according to the formula ratio. The mixer speed is increased to 200 r / min. Mixture C is added and stirred for 3 h to obtain the coating.
[0034] A preparation process of a high-toughness carbon steel composite plate, the specific process of the preparation process of the high-toughness carbon steel composite plate is as follows.
[0035] S3.1: Place the inner carbon steel layer and the middle stainless steel layer in a vacuum sealed environment and weld them together. The welding parameters are: welding vacuum degree ≤ 1.0Pa, welding current 100A, welding depth 50mm under argon atmosphere; S3.2: After welding, the surface of the middle layer stainless steel is polished and ground. The polishing parameters are: first use a grinding head composed of 500 mesh elastic modules to grind at 2MPa for 1h, then use a grinding head composed of 2000 mesh elastic modules to grind at 0.3MPa for 0.5h. After grinding, use 10m / s nitrogen to purge. After purging, use the spraying method to evenly spray the outer toughness coating on the surface of the middle layer stainless steel. The spraying parameters are spraying distance 100mm, spraying rate 60 mm / s, and standing for 2h. S3.3: The coating is dried by a laser drying method, the parameters of which are a laser power of 300 W, a temperature of 60°C, and an irradiation time of 30 min. The coating is then further subjected to hot pressing treatment, the parameters of which are a temperature of 70°C, an applied force of 15 KN, and a hot pressing time of 120 s. After hot pressing, hydrogen at 80°C is first used for purging, the hydrogen purging flow rate is 20 m / s, and the purging time is 1 h. Then, nitrogen at 80°C is used for purging, the purging time is 0.5 h, and the nitrogen purging flow rate is 20 m / s, to obtain the high-toughness carbon steel composite plate.
[0036] Comparative Example 1 In this comparative example, no coating is sprayed on the surface, and the remaining steps are consistent with those in Example 1.
[0037] Comparative Example 2 In this comparative example, the coating is not subjected to laser drying treatment, and the remaining steps are consistent with those in Example 1.
[0038] Comparative Example 3 In this comparative example, the coating is not subjected to heat pressing treatment, and the remaining steps are consistent with those in Example 1.
[0039] Comparative Example 4 In this comparative example, the stainless steel surface is not polished or ground, and the remaining steps are consistent with those in Example 1.
[0040] The tensile test was carried out on the embodiments and comparative examples according to GB / T 228.1-2021. The experimental data are summarized in the following table: The wear resistance of the embodiment and the comparative example was tested by using a JM IV abrasion tester and a rotating friction rubber wheel method. The wear resistance of the present invention was measured by the average value of the sample loss (weight loss method) after 100 grinding revolutions. The load was 10 N, the rotation speed was 80 r / min, the test temperature was 25 ° C, the relative humidity was 50%, and the mass was tested to an accuracy of 0.01 mg. The average value of 3 measurements was taken as the result. The test results are summarized in the following table.
[0041] It can be seen from experimental data that the high-toughness carbon steel composite plate prepared by the present invention has better tensile strength and wear resistance.
[0042] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A high-toughness carbon steel composite plate, characterized in that: The carbon steel composite plate comprises an inner layer of carbon steel, a middle layer of stainless steel plate and an outer layer of tough coating. The outer toughness coating has a formula of 20-30% copper-zinc-nickel compound, 20-30% tungsten carbide, 20-30% natural rubber, 10-15% ethanolamine, and 10-15% deionized water, by mass percentage. The preparation method of the copper-zinc-nickel composite is as follows: S1.1: Copper nitrate pentahydrate, zinc nitrate hexahydrate, and nickel nitrate hexahydrate are mixed in a mass ratio of 5:2:3, and ground at a speed of 300 r / min for 15-30 min, and then 2-3 wt% oxalic acid monohydrate is added, and the grinding is continued for 10-15 min to obtain a uniform and viscous mixture A; S1.2: Mix the mixture A and aqueous ammonia with a concentration of (0.5-1) mol / L in a mass ratio of 1:1, ultrasonicate for 30 min, and dry at 110 °C for 12 h to obtain a mixture B; S1.3: The mixture B is heated from room temperature to 200°C, kept at a constant temperature and then roasted for 1-2 hours, then heated to 350°C, kept at a constant temperature and then roasted for 1 hour, and after roasting, it is crushed and ground to obtain a copper-zinc-nickel composite; The outer toughness coating preparation method is as follows: S2.1: Mix the copper-zinc-nickel composite and tungsten carbide according to the formula ratio, put them into a ball mill and grind them at a speed of 400 r / min for 2 hours to obtain a mixture C; S2.2: Heat the natural rubber to 130-140° C., stir it in a stirrer at a speed of 150 r / min for 1-2 h, add ethanolamine and deionized water according to the formula ratio, increase the stirrer speed to 200 r / min, add mixture C, stir for 3-4 h, and obtain the coating.
2. The high-toughness carbon steel composite plate according to claim 1, characterized in that: The rate of heating from room temperature to 200°C in S1.3 is 5°C / min.
3. The high-toughness carbon steel composite plate according to claim 1, characterized in that: The rate of heating from 200°C to 350°C in S1.3 is 3°C / min.
4. The high-toughness carbon steel composite plate according to claim 1, characterized in that: The copper-zinc-nickel composite obtained in S1.3 has a particle size of 100 mesh.
5. The high-toughness carbon steel composite plate according to claim 1, characterized in that: The particle size of the mixture C in S2.1 is 200 mesh.
6. A process for preparing a high-toughness carbon steel composite plate, based on a high-toughness carbon steel composite plate according to any one of claims 1 to 5, characterized in that: The specific process of the preparation process of the high-toughness carbon steel composite plate is as follows: S3.1: Place the inner carbon steel and the middle stainless steel in a vacuum sealed environment and weld them together. The welding parameters are: welding vacuum degree ≤ 1.0Pa, welding current 80~100A, welding depth 50~80mm under argon atmosphere; S3.2: After welding, the surface of the middle layer stainless steel is polished and ground. After polishing, it is purged with 10m / s nitrogen. After purging, the outer toughness coating is evenly sprayed on the surface of the middle layer stainless steel by spraying method and left to stand for 1~2h; S3.3: The coating is dried by a laser drying method, and then further hot-pressed by a hot pressing method. The hot pressing parameters are a temperature of 60-70°C, an applied force of 10KN-15KN, and a hot pressing time of 120-300s. After hot pressing, it is first purged with 80°C hydrogen for 1 hour, and then purged with 80°C nitrogen for 0.5 hours to obtain the high-toughness carbon steel composite plate.
7. The process for preparing a high-toughness carbon steel composite plate according to claim 6, characterized in that: The polishing parameters in S3.2 are as follows: first, use a grinding head composed of 500-mesh elastic modules to polish at 1-2 MPa for 1 hour, and then use a grinding head composed of 2000-mesh elastic modules to polish at 0.3-0.5 MPa for 0.5 hour.
8. The process for preparing a high-toughness carbon steel composite plate according to claim 6, characterized in that: The spraying parameters in S3.2 are spraying distance 100 mm and spraying rate 60 mm / s.
9. The process for preparing a high-toughness carbon steel composite plate according to claim 6, characterized in that: The parameters of the laser drying in S3.3 are: laser power 260-300 W, temperature 50-60° C., and irradiation time 20-30 min.
10. The process for preparing a high-toughness carbon steel composite plate according to claim 6, characterized in that: The purge flow rate of hydrogen and nitrogen in S3.3 is 20 m / s.
Citation Information
Patent Citations
Method for preparing silicon oxide ceramic coatings on steel member through electrophoretic deposition
CN102732936A
Anti-corrosion and anti-abrasion method of hydraulic turbine blade organic coating
CN106513288A
Metal part surface processing technology for improving corrosion resistance
CN112844995A
Coating method of ceramic coating for relief etching pot
CN119346405A